Protective Effects of Cod Skin Collagen Peptides against Chronic Alcoholic Liver and Brain Injury in Mice - CHEN Chen, GUO Jiaqi, KONG Songzhi, XIE Haisheng, LIANG Meiyin, CHEN Jinhui, LI Zirui (Shipin Kexue, 2025)
In this study, a mouse model of chronic alcohol-induced liver and brain injury was established through prolonged intragastric administration of an alcohol solution. By comparing biochemical parameters and histopathological findings in liver and brain tissues across different experimental groups, we investigated the effects of codfish skin polypeptides on chronic alcohol-induced organ damage and the underlying mechanisms. The results demonstrated that, compared with the model group, treatment with codfish skin polypeptides significantly reduced serum triglyceride (TG) levels and the activities of aspartate aminotransferase (AST) and alkaline phosphatase (ALP). It also enhanced the activities of alcohol dehydrogenase (ADH), aldehyde dehydrogenase (ALDH), glutathione peroxidase (GSH-Px), and catalase (CAT) in liver tissue, and effectively inhibited the overexpression of inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-8 (IL-8), while reducing cytochrome P450 (CYP450) content. In brain tissue, codfish skin polypeptides increased the levels of acetylcholine transferase (ChAT) and brain-derived neurotrophic factor (BDNF), suppressed the overexpression of key inflammatory factors including TNF-α, interleukin-1β (IL-1β), interleukin-6 (IL-6), and nicotinamide phosphoribosyltransferase (NAMPT), inhibited inducible nitric oxide synthase (iNOS) and nitric oxide (NO) synthesis, elevated glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and catalase (CAT) activities, and decreased cholinesterase (AChE), monoamine oxidase B (MAO-B), malondialdehyde (MDA), and reactive oxygen species (ROS) levels. Histopathological examination revealed that, compared with the model group, the liver structure of codfish skin polypeptides-treated mice was clearer with better organized hepatic lobules, less hydropic and fatty degeneration of hepatocytes, and reduced collagen fiber deposition. These findings suggest that codfish skin polypeptides alleviate alcohol-induced oxidative stress and inflammatory responses in both liver and brain tissues by modulating the NF-κB signaling pathway and the NF-κB/iNOS-NO signaling pathway, respectively. Additionally, these polypeptides promote ethanol metabolism by enhancing the activity of hepatic ethanol-metabolizing enzymes and positively regulate the central nervous system to maintain neurotransmitter balance, thereby effectively mitigating alcohol-induced liver and brain injury.